Expression of FK506‐binding protein 51 (FKBP51) in Mycosis fungoides. (9th November 2017) - Mascolo, M.; Romano, M.F.; Ilardi, G.; Romano, S.; Baldo, A.; Scalvenzi, M.; Argenziano, G.; Merolla, F.; Russo, D.; Varricchio, S.; Pagliuca, F.; Russo, M.; et al.
Abstract: Background: Mycosis fungoides (MF) is the major subtype of cutaneous T‐cell lymphomas (CTCL). It usually has a prolonged indolent clinical course with a minority of cases acquiring a more aggressive biological profile and resistance to conventional therapies, partially attributed to the persistent activation of nuclear factor‐kappa B (NF‐κB) pathway. In the last decade, several papers suggested an important role for the FK506‐binding protein 51 (FKBP51), an immunophilin initially cloned in lymphocytes, in the control of NF‐κB pathway in different types of human malignancies. Objectives: We aimed to investigate the possible value of FKBP51 expression as a new reliable marker of outcome in patients with MF. Methods: We assessed by immunohistochemistry (IHC) FKBP51 expression in 44 patients with MF, representative of different stages of the disease. Immunohistochemical results were subsequently confirmed at mRNA level with quantitative PCR (qPCR) in a subset of enrolled patients. In addition, IHC and qPCR served to study the expression of some NF‐κB‐target genes, including the tumour necrosis factor receptor‐associated factor 2 (TRAF2). Results: Our results show that FKBP51 was expressed in all evaluated cases, with the highest level of expression characterizing MFs with the worst prognosis. Moreover, a significant correlation subsisted between FKBP51 and TRAF2 IHC expression scores. Conclusions: We hypothesize a role for FKBP51 as a prognostic marker for MF and suggest an involvement of this immunophilin in deregulated NF‐κB pathway of this CTCL.